2022
DOI: 10.3390/agriculture12040541
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Influence of the Channel Layout and Size on the Hydraulic Performance of Emitters

Abstract: In this paper, a split-flow channel layout with one (group) inlet and two (group) outlets is adopted, based on computational fluid dynamics technology, and compared with the current commonly used channel with one (group) inlet and one (group) outlet emitter. On the premise of the same outlet spacing, the pressure–flow relationship curve and slope of the split-flow emitter were analyzed under the three channel layouts of non-return, single-sided re-entry, and bilateral re-entry, with different channel widths an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…We analyzed the simulation results of the emitter flow field under each structural parameter in the range of 5 to 15 mH 2 O inlet pressure, calculated the flow coefficient k and flow state index x, and fitted to obtain the pressure-flow relationship curve. The pressure-flow relationship curve slope for each emitter at different working pressures was calculated according to [44]:…”
Section: Results and Analysismentioning
confidence: 99%
“…We analyzed the simulation results of the emitter flow field under each structural parameter in the range of 5 to 15 mH 2 O inlet pressure, calculated the flow coefficient k and flow state index x, and fitted to obtain the pressure-flow relationship curve. The pressure-flow relationship curve slope for each emitter at different working pressures was calculated according to [44]:…”
Section: Results and Analysismentioning
confidence: 99%
“…Clogging primarily occurs in the emitters of subsurface drip irrigation systems and is caused by particle blockage, deposition from chemical reactions between fertilizers, and the aggregation of microorganisms in confined spaces [74]. Regular flushing or periodic flushing can effectively prevent clogging in pipelines and emitters [75]. The anticlogging performance of emitters depends on factors such as channel shape, dimensions, materials, and other factors.…”
Section: Discussionmentioning
confidence: 99%
“…Celik et al [14] conducted experimental and CFD analysis of the flow characteristics of labyrinth-channel emitters and found that the channel's corner structure could improve the hydraulic performance of the emitter. Du et al [15] found that changing the flow path of the emitter from one inlet and one outlet to one inlet and two outlets resulted in better hydraulic performance. Patil et al [16] studied labyrinth emitters with five different tooth shapes and found that the tooth structure has a greater effect on the vortex in the flow field, and pointed out that a reasonable boundary structure can increase the energy dissipation in the channel.…”
Section: Introductionmentioning
confidence: 99%